Preparation of Nanoemulsions of Vitamin A and C by Microfluidization: Efficacy on the Expression Pattern of Milk-Specific Proteins in MAC-T Cells - Kim, Tae-Il (Molecules, 2019)
In this study, we prepared stabilized vitamin A and C nanoemulsions, and investigated their efficacy on milk-specific proteins in bovine mammary epithelial cells (MAC-T). Emulsions of vitamin A (vit-A) and C (vit-C) were prepared using Lipoid S 75 and microfluidization. The particle size and polydispersity index (PDI) of nanoemulsified vit-A and vit-C were studied. The cytotoxic effect of nanoemulsion-free and nanoemulsified vit-A and vit-C was determined by an MTT assay. In addition, the efficacy of nanoemulsified vit-A and vit-C on the in vitro expression pattern of milk-specific proteins in MAC-T cells was investigated by quantitative RT-PCR. The results showed that the efficacies of stabilized nanoemulsions of vit-A and vit-C were 100% and 92.7%, respectively. The particle sizes were around 475.7 and 225.4 nm, and the zeta potentials were around −33.5 and −21.3 mV, respectively. The expression changes of α(s2)-, β- and κ-casein were higher in the presence of a stabilized nanoemulsion of vit-A, compared with nanoemulsion-free vit-A. Furthermore, the expression changes of α(s2)- and β-casein were lower and that of κ-casein was higher in the presence of a stabilized nanoemulsion of vit-C, compared with nanoemulsion-free vit-C. Thus, our findings demonstrate the efficacy of nanoemulsified vit-A and vit-C in changing the expression of milk-specific proteins in MAC-T cells.